Chronic Myelomonocytic Leukemia following Multicentric Castleman Disease. (23rd January 2018) - Li, Feng; Zhang, Xiaomei; Guo, Yanting; Zhu, Yuandong; Wu, Yicun; Ling, Yun
Abstract : Multicentric Castleman disease (MCD) is a rare nonmalignant lymphoproliferative disorder presenting systemic symptoms such as fever, night sweats, fatigue, anemia, effusions, and multifocal lymphadenopathy. The etiology of MCD has not been clarified to date. The coexistence of MCD with chronic myelomonocytic leukemia (CMML) has been rarely reported. Although the pathogenesis remains unclear, this association probably reflects an incidental and fortuitous finding rather than the alteration of a common pluripotent stem cell precursor. Herein, we report on one case of MCD coexisting with CMML and elucidate the underlying mechanism of pathology in some aspects.